2004
DOI: 10.1016/j.jtcvs.2003.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Late incidence and predictors of persistent or recurrent heart failure in patients with aortic prosthetic valves

Abstract: These analyses identify independent predictors of congestive heart failure symptoms and congestive heart failure death late after aortic valve replacement and indicate that prosthesis size has a significant effect on this cardiac end point, but not on overall survival after aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
125
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 26 publications
2
125
3
Order By: Relevance
“…3,13 Indexed EOA was calculated by using the patients' body surface area at the time of operation. Prosthesis-patient mismatch (PPM) was defined as an indexed EOA ≤0.85 cm 2 /m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,13 Indexed EOA was calculated by using the patients' body surface area at the time of operation. Prosthesis-patient mismatch (PPM) was defined as an indexed EOA ≤0.85 cm 2 /m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The outcomes of AVR have improved over the last decade, 1 but the incidence and mortality of congestive heart failure (CHF) after AVR remain high among patients with left ventricular (LV) dysfunction. [3][4][5] One possible mechanism is nonrecovery of LV dysfunction after AVR. Because LV function affects clinical outcomes, 3,6 incomplete LV recovery postoperatively may translate into decreased survival and quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors pointed out that PPM might have been found to have a significant effect in the normal LV function cohort had they evaluated cases with severe mismatch (≤ 0.65 cm 2 / m 2 ). An earlier study by Ruel et al (2004) had shown that although PPM had significant effects on cardiac end points (occurrence of congestive heart failure, etc), it had no effect on overall survival after AVR. Kulik et al (2006) found that patients with low-gradient aortic stenosis (LGAS, defined as an aortic valve area of < 1.2cm 2 , a mean transvalvular pressure gradient of < 40 mmHg, and a LVEF of < 50%) have worse long-term outcomes after AVR, and that PPM further adversely affects the long-term outcomes of LGAS patients and should therefore be avoided in this population.…”
Section: Carpentier-edwardsmentioning
confidence: 98%
“…This discordance is due in fact to different ways of evaluating EOA. As a whole, studies based on an in vivo evaluation of the indexed EOA tend to report clinical implications (Blais et al, 2003, Ruel et al, 2004, Tasca et al, 2006. In the contrary, the in vitro evaluation of the indexed EOA tends to underestimate clinical implications of PPM (Koch et al, 2005).…”
mentioning
confidence: 99%